Experiencing images in museums: An Approach to the Relationships between the Museum, the Image and the Senses - Pazos-López, Ángel; Alonso Tak, Alejandra (Eikón / Imago, 2019)
Leader article of Museum. Image. Senses. The monography examines, through a score of scientific articles, the relationships between visual and sensory experience in museums. To do this, it brings together works related to art history, visual theory, communication, cultural and social action in museums, as well as new museological projects that aim to bring art closer to a growing diversity of people.